Hak dan Kewajiban Sumber Daya Manusia dalam Perspektif Manajemen SDM: Studi Literatur - Nisa saskia Febriyanti (Prodi Manajemen, 2025)
This study examined human resource rights and obligations from a human resource management perspective as a fundamental basis for effective and sustainable organizational management. The imbalance between the fulfillment of employee rights and the implementation of employee obligations had become a critical issue affecting work motivation, loyalty, and organizational performance, particularly in public organizations. This study aimed to review and synthesize concepts, findings, and theoretical frameworks related to human resource rights and obligations using a qualitative approach with a literature study method. Data were collected from relevant academic sources, including scholarly journal articles and scientific books, and were analyzed through data reduction, classification, and thematic synthesis. The findings indicated that the fulfillment of human resource rights and the execution of human resource obligations were complementary and inseparable elements in human resource management practices. A balanced integration of these aspects contributed to harmonious employment relations, improved performance, and organizational sustainability. This study concluded that human resource rights and obligations should be positioned as a strategic foundation in the formulation of human resource management policies and practices.